Pengaruh Penggunaan Pelat Elektroda Tekstur terhadap laju Produksi gas pada Generator HHO - Asmawi Asmawi; MUHD. Ridzuan bin Mansor; Noreffendy Tamaldin; Viktor Vekky Ronald Repi; Ajat Sudrajat (Universitas Nasional, 2022)
SS316L iron plate is a material that is often used in construction on machinery. In this study, 6 sheets of SS316L plates as electrode plates measuring 100 mm × 100 mm were assembled into a spacer shape arranged parallel to the distance of 2 mm. The SS316L electrode plate consists of two types, namely the original electrode plate or flat plate and the electrode plate through a treatment process where the surface is made of lines (texture). Both flat and textured electrode plate is formed into a spacer which then inserted to the HHO generator as the main component in the water electrolysis process. Measurements and calibrations are performed on each HHO generator with flat electrode plates and textured electrode plates with KOH catalyst 10 grams, 20 grams and 30 grams. The results of the calibration of the two types of HHO generators show that the HHO generator with texture plates is better than the flat plate with an average value of 1.03 L/minute.